Implementation Of Tadabbur Al-Qur'ân Surah Al-Fâtihah In Constitutional Political Education - Amang Syafrudin; Didin Saefudin; Endin Mujahidin; Ibdalsyah Ibdalsyah (Journal of Social Research, 2024)
Surah Al-Fâtihah, as the greatest surah in the Qur'an, can be obtained, evaluated and tested for the truth of its knowledge through five levels of understanding (Fiqh), namely: Fiqh al-Lughah (Language and the Nature of Knowledge), Fiqh al-Munâsabah (Correlation and Building Structure of Knowledge), Fiqh al-Hidâyah (Instructions and Methods for Obtaining and Testing the Truth of Knowledge), Fiqh al-Idârah (how to Manage the Benefits, Solutions and Neutrality of Knowledge), and Fiqh al-Hadârah (ways of Knowledge solve the problem). The tadabbur analysis of Surah Al-Fâtihah was carried out using an integration approach of three perspectives, namely: First, the perspective of the Philosophy of Science, Second, the perspective of Bloom's Taxonomy regarding the Dimensions of Knowledge, and Third, the perspective of the Tadabbur Methodology. Through a combination of the three perspectives, it can be formulated that Surah Al-Fâtihah is a surah which means Opener, has a philosophy of meaning of victory (Al-Fath) based on openness; both thoughts, heart (beliefs and emotions), and attitudes (behavior and morals). In the context of Constitutional Politics, this Surah inspires constitutionalism as the spirit needed in the formation of a Constitution. Up to the level of the Living Constitution which contributed to the civilization of all humans in the world. This research aims to determine the concept of implementing the Quranic tadabur Surah Al-Fatihah in constitutional politics